Russland im Spiegel der Medien Eine Diskursanalyse der deutschen Presse 1999 bis 2016 - Schmidt, Danny (Internationale und Interkulturelle Kommunikation, 2022)
Is Russia a fearful giant, an economic partner or a belligerent aggressor? The answer to this question depends on the perspective. What perspectives and consequently what answers does the German press landscape have to offer? What does the reporting on ""Putin's Russia"" look like in Germany? And how diverse is it? Danny Schmidt analyses how leading German media write about Russia. Articles from the Frankfurter Allgemeine Zeitung, Neues Deutschland, Der Spiegel, Süddeutsche Zeitung and Welt paint a clear picture. The perspective is narrowed, the diversity of perspectives reduced, a neutral view not always given. Historical discourses reactivate stereotypes and fuel resentment. The result is the construction of a vital image of the enemy, which has become a sad reality in the war in Ukraine.